2009
DOI: 10.1158/0008-5472.can-09-1089
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Transcriptome Analysis Reveals Common Molecular Subclasses of Human Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a highly heterogeneous disease, and prior attempts to develop genomics-based classification for HCC have yielded highly divergent results, indicating difficulty to identify unified molecular anatomy. We performed a meta-analysis of gene expression profiles in datasets from 8 independent patient cohorts across the world. In addition, aiming to establish the real world applicability of a classification system, we profiled 118 formalin-fixed, paraffin-embedded tissues from an add… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

58
1,095
2
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,036 publications
(1,207 citation statements)
references
References 40 publications
58
1,095
2
10
Order By: Relevance
“…This is partly due to a lack of effective chemotherapeutic options for patients with advanced-stage disease [3]. Various molecular profiling approaches have been used to identify potential therapeutic targets which are specifically activated in HCC [4][5][6][7][8]. Some studies have indicated the importance of evaluating ''stemness'' in HCC; it reflects the malignant nature of the tumor and closely correlates with a poor prognosis after surgery [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…This is partly due to a lack of effective chemotherapeutic options for patients with advanced-stage disease [3]. Various molecular profiling approaches have been used to identify potential therapeutic targets which are specifically activated in HCC [4][5][6][7][8]. Some studies have indicated the importance of evaluating ''stemness'' in HCC; it reflects the malignant nature of the tumor and closely correlates with a poor prognosis after surgery [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The past decade has seen multiple negative trials, many of which have not been guided by our understanding of genetic pathways in HCC. Current efforts should be directed toward the development of biomarker-enriched clinical trials, as well as drugs that target key oncogenic pathways with a better understanding of the tumor biology and genetics (65)(66)(67).…”
Section: Resultsmentioning
confidence: 99%
“…The subtypes are distinguished by high proliferation and chromosomal instability; by activation of Wnt signalling pathway and by interferon signalling due to tumour-infiltrating cells [70][71][72][73][74][75][76][77].…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%